Extreme teams why Pixar, Netflix, AirBnB, and other cutting-edge companies succeed where most fail - Shaw, Robert Bruce (American Management Association, 2017)
Great achievements are almost always the work of a great team. But most leaders rely on decades-old ideas and practices about teams developed by companies that have lost their edge. Times change and so must our teams. Those who cling to outdated views of teamwork and team building will be left behind. So what do you need to do to create a team that can successfully face the challenges of today's world? To answer that question, Robert Bruce Shaw examines the work practices of innovative high-growth companies such as Whole Foods, Pixar, and Netflix. These firms became groundbreaking leaders in their industries, in part, by boldly rewriting the rules of teamwork. Extreme Teams provides a detailed analysis of how the leaders at these companies think and operate--and, in particular, describes their approaches for creating high energy teams that deliver extraordinary results. You will learn in Extreme Teams: how Alibaba strives to hire the right people--not the best people; why co-workers determine if you stay or go at Whole Foods; the benefit to Airbnb of letting its employees determine the projects on which they work; how employees at Patagonia have nearly complete control over their work and play hours; what Pixar does to avoid repeating what worked for it in the past; why Netflix rewards average performance with a generous severance package; what will get you fired at Zappos--and it's not what you think. Filled with success stories from some of the most exciting firms operating today, Extreme Teams will push you to think about teams in new ways. It is filled with pragmatic suggestions that you can use to move your team to the next level of engagement and performance. This is the book for those who want to go beyond traditional approaches to teamwork and build truly great groups. -- Inside jacket flaps.
Includes bibliographical references and index. - Print version record and CIP data provided by publisher
Keywords: Teams in the workplace; Équipes de travail; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior